Bacterial metabolites influence the autofluorescence of Clostridioides difficile - Ticer, Taylor D.; Tingler, Anna M.; Glover, Janiece S.; Dooley, Sarah A.; Kendrick, Jacob; Zackular, Joseph P.; Devkota, Suzanne; Wu, Gary D.; Mahalak, Karley; Engevik, Amy; Engevik, Melinda A. (Frontiers in Microbiology, 2024)
Clostridioides difficile is a bacterial pathogen that has been implicated in severe gastrointestinal infections. C. difficile has intrinsic green autofluorescence and the level of this autofluorescence is known to be increased by growth time and oxygen. Currently, it is unclear if dietary compounds or metabolites from the gut microbiota are able to enhance C. difficile autofluorescence. Here, we aimed to determine potential factors that affect C. difficile autofluorescence. After screening a large repertoire of compounds, we identified several substances, like L-lysine and pantothenate, that led to an increased C. difficile autofluorescence. We also found that several members of the gut microbiota, such as Enterococcus faecalis, Klebsiella aerogenes and K. pneumoniae, can increase C. difficile autofluorescence through their secreted compounds. We further focused on the effect of K. pneumoniae on C. difficile autofluorescence and found that multiple enteric strains of K. pneumoniae could enhance C. difficile’s autofluorescence. We used this enhanced autofluorescence to identify C. difficile in K. pneumoniae co-cultures by flow cytometry. Our findings shed light on the relationship between C. difficile and other members of the gut microbiota, as well as different factors that can affect C. difficile autofluorescence.